Linking Formal and Non-Formal Learning in Science Education - A Reflection from Two Cases in Ireland and Germany - Nicole Garner; Sarah M. Hayes; Ingo Eilks (Universidade de Lisboa, 2014)
This paper discusses two cases of linking formal and non-formal learning in science education. The cases concern science education in the Irish Transition Year, a facultative year between lower and upper secondary education, and a non-formal laboratory learning environment for lower and upper secondary school students in a German university. Both cases are described, compared and jointly reflected on non-formal education's potential and limitations for supporting formal science learning.